2017
DOI: 10.1016/j.sbi.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Structural biology of the core autophagy machinery

Abstract: In autophagy, which is an intracellular degradation system that is conserved among eukaryotes, degradation targets are sequestered through the de novo synthesis of a double-membrane organelle, the autophagosome, which delivers them to the lysosomes for degradation. The core autophagy machinery comprising 18 autophagy-related (Atg) proteins in yeast plays an essential role in autophagosome formation; however, the molecular role of each Atg factor and the mechanism of autophagosome formation remain elusive. Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 62 publications
2
96
0
Order By: Relevance
“…Also, it can be activated through IRE1-JNK pathway [45]. Activation of IRE1 stimulates disruption of Beclin-1 inhibitory complexes through phosphorylation of Bcl-2, thereby triggering autophagy [46]. And the results in this study revealed both inhaling H2 and ischemic postconditioning could reduce the expressions of Bclin-1 and –Bcl-2/ Bcl-2 induced by I/R injury, besides, inhaling H 2 had a better effect in reducing the expression of these proteins when compared with ischemic postconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it can be activated through IRE1-JNK pathway [45]. Activation of IRE1 stimulates disruption of Beclin-1 inhibitory complexes through phosphorylation of Bcl-2, thereby triggering autophagy [46]. And the results in this study revealed both inhaling H2 and ischemic postconditioning could reduce the expressions of Bclin-1 and –Bcl-2/ Bcl-2 induced by I/R injury, besides, inhaling H 2 had a better effect in reducing the expression of these proteins when compared with ischemic postconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the beclin-1/vacuolar protein sorting 34 (BECN-1/Vps34) complex is recruited to catalyze the formation of phosphatidyl-inositol-3-phosphate (PI3P) [9], necessary for the formation of the preautophagosomal membrane or phagophore. The elongation of this structure is regulated by the sequential and coordinated action of autophagy-related (ATGs) proteins, leading to the formation of the autophagosome [9,10], the double-membrane bound vesicle that sequesters autophagic cargo on its lumen. Hence, ATG-3, ATG-4, and ATG-7 catalyze the lipidation of microtubule-associated light chain 3 (LC3), which accumulates in autophagosomal membranes and mediates cargo engulfment by binding to autophagic substrates.…”
Section: Autophagy: the Factsmentioning
confidence: 99%
“…Autophagy is mainly regulated by a step-wise process including the formation of autophagosome (a double-membrane organelle), docking and fusion of autophagosome with lysosome/vacuole and proteases-mediated degradation of the cargos (27). A set of autophagy-related (ATG) proteins have been reported to function in different stages of autophagy (27,28). To test whether autophagy pathway regulates Rph1 degradation upon DNA damage stress, cells were treated with a protease inhibitor, Phenylmethanesulfonyl fluoride (PMSF), to block vacuolar proteolysis.…”
Section: Resultsmentioning
confidence: 99%